Galeri Seni Di Pekanbaru Dengan Pendekatan Arsitektur Art Deco - Hazrati Sharfina; Wahyu Hidayat; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru is the city that is open to the development of art and culture. It can be seen from many art activities are held. According to its development, the arts in Riau, especially Pekanbaru City still lack a place that can accommodate the activities of the art. It needs a place of art gallery as a place to express their emotion into a work of art and art gallery as well as a place of learning for the city of Pekanbaru. Development of Pekanbaru nowadays, modern buildings began to appear, but still using Riau Malay carving decoration, therefore, this art gallery will be designed by applying the method of Tropical Deco architecture, that also uses carved decoration as its characteristics, so it can adapt to surrounding building. In order to design art gallery is designed by applying Tropical Deco as concept, the characteristics of art deco architecture that are customized to the natural tropical conditions like Pekanbaru City area. The result of those application are implemented in the design of the Art Gallery such as zoning, the order of mass, outer space, shape of mass, interior space, and building facades.Keywords: Art Deco Architecture, Art Gallery, Tropical deco